A generalized estimator for finite population mean in the presence of measurement errors in stratified random sampling. (3rd April 2018) - Khalil, Sadia; Gupta, Sat; Hanif, Muhammad
ABSTRACT: A generalized estimator is introduced for finite population mean in stratified random sampling when observations are contaminated with measurement errors. Many special cases of the proposed estimator are possible. The bias and mean square error of the proposed family of estimators are derived. The performance of the proposed estimator is evaluated both theoretically and empirically in the presence and absence of measurement error.